Clinical and Demographic Characteristics of Transgender Individuals with Hysterectomy and Bilateral Salpingo oophorectomy: Experience of a Tertiary Center - Canbolat, Kübra Hamzaoğlu; Yıldırım, Hilal Atılgan; Tüten, Abdullah (Cerrahpaşa Medical Journal, 2024)
Objective: We evaluated the demographic and clinical characteristics and surgical complications of patients who had undergone laparoscopic hys terectomy and bilateral salpingo-oophorectomy (BSO) for gender dysphoria in our tertiary center. Methods: This retrospective cohort study was conducted between 2015 and 2020. A total of 204 people who applied for gender dysphoria according to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition criteria and underwent total hysterectomy and BSO were included in the study. Demographic and clinical findings and perioperative complications were noted. Results: The age of the patients was between 21 and 55, and their body mass index was between 21 and 32. 86.2% of the patients were single. About 94.1% of patients were smoking. While 5.8% of them were university graduates, 1.9% have never been to school. About 87.3% of them did not have any systemic diseases. Perioperative complications occurred in a total of 9 patients (3.6%). These were blood transfusions (n = 2, 0.8%), vaginal cuff bleeding (n = 1, 0.4%), postoperative voiding dysfunction (n = 1, 0.4%), ureteral injury (n = 1, 0.4%), ileus (n = 1, 0.4%), and urinary tract infection (n = 3, 1.2%). Conclusion: Most of these people are healthy people who are single, smokers, and high school graduates. Hysterectomy and BSO surgery, when performed as part of gender-affirming treatment, are widely recognized as effective and reliable methods. Cite this article as: Hamzaoğlu Canbolat K, Atılgan Yıldırım H, Tüten A. Clinical and demographic characteristics of transgender indi viduals with hysterectomy and bilateral salpingo-oophorectomy: Experience of a tertiary center. Cerrahpaşa Med J. 2024;48(1):26-29.